Strengthening the Pedagogical Competence of Social Studies Teachers via Training in the Preparation and Test Items Analysis Utilizing The ANBUSO Application - Musyarofah Musyarofah; Novita Nurul Islami; Maulidatusy Syahrisy Syarifah; Nivayatus Sayyadah; Alfira Intan Dwi Cahyani (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
Training on the preparation and analysis of test items using the ANBUSO application was conducted to the social studies teachers of MGMP SMP/MTs Jember Regency at UIN Kiai Haji Achmad Siddiq Jember. Based on the results of the initial Focus Group Discussion (FGD) conducted by the service team with the Social Studies Teacher Consultation Group SMP / MTs in Jember Regency, the partners are confronted with a problem that the MTs/SMP social studies teachers’ capacity to plan and produce reports on the outcomes of learning evaluation is insufficient. The aims of this service activity are as follows: a) describe the execution of training procedures of learning evaluation preparation, formulation of test items, and item analysis utilizing the ANBUSO application for social studies teachers of SMP/MTs in Jember Regency; b) describe the execution of item analysis assistance utilizing the ANBUSO application for social studies teachers of SMP/MTs in Jember Regency; c) determine the level of success of activities to strengthen the pedagogical competence of social studies teachers of SMP/MTs through training of preparation and item analysis using the ANBUSO Application. d) describe the results of the evaluation of service activities. The method employed in this service activity is the PAR (Participatory Action Research) through several stages including: Mapping and problem identification, FGD and problem analysis, Program preparation stage, program socialization, program implementation, monitoring, and program evaluation. The implementation of this community service activity consists of the following stages: (1) providing training materials consisting of the concept of learning evaluation, procedures for preparing learning evaluations, especially in the Merdeka curriculum, preparing test questions and test items analysis; (2) analyzing test items using the ANBUSO application. The results of the theoretical test in the form of a pre-test and post-test indicate that the post test data shows a significant increase, namely 91% passed with a score above 70 and the remaining 9% failed with a score below 70. Evaluation is also carried out by assessing the results of practices that have been successfully carried out by the participants.